Preparation and application of CuNPs / S-GS / PDMS flexible piezoresistive sensor
Patent Information
- Application Number
- CN202510827709.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-20
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2045-06-20
AI Technical Summary
然而,现有替代方案仍面临导电网络稳定性不足、灵敏度与检测范围难以兼顾等挑战,尤其在阵列化传感器集成方面尚未形成高效的系统解决方案
3.在施加80 kPa的压力时,传感器的响应时间为0.6 s,卸载时间为0.81 s,并在压缩释放2000次的循环实验中具有极好的重复性和稳定性,较S-GS/PDMS复合泡沫压阻传感器皆有明显提升。这些优异的性能使该传感器能够实时监测人体关节的活动,具有广泛的应用前景。
Smart Images

Figure CN120702637B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sensor technology, specifically to a method for fabricating a CuNPs / S-GS / PDMS flexible piezoresistive sensor. Background Technology
[0002] Flexible piezoresistive sensors, due to their excellent deformation adaptability, fast response characteristics, and durability, have significant application value in human physiological monitoring (such as pulse detection and motion sensing) and engineering safety monitoring (such as pipeline stress detection). In existing technologies, flexible piezoresistive sensors based on polydimethylsiloxane (PDMS) composites with conductive materials have become a research hotspot. For example, the invention patent with authorization announcement number CN112086553B proposes a three-dimensional interconnected graphene microchannel embedded PDMS sensor, which significantly improves the sensor's sensitivity (up to 53.7 kPa) by depositing noble metal nanoparticles (gold, silver, or platinum) on the inner wall of the graphene microchannel. -1 It features both pressure and strain monitoring capabilities and dual-mode detection. However, this technology has the following limitations: High material costs: The use of precious metal nanoparticles (gold, silver, platinum) significantly increases manufacturing costs, which is not conducive to large-scale commercial applications; The process is complex and environmentally unfriendly: it relies on chemical vapor deposition (CVD) to grow graphene and requires the use of highly corrosive FeCl3 solution to remove the foamed nickel template, which is cumbersome and generates polluting waste liquid. Functional limitation: The sensor structure is a single-point unit, lacking array design, making it difficult to achieve real-time monitoring of spatial pressure distribution.
[0003] To overcome these problems, recent studies have attempted to optimize the process using low-cost materials (such as copper nanoparticles) and simple template methods (such as sugar templates). However, existing alternatives still face challenges such as insufficient stability of the conductive network and the difficulty in balancing sensitivity and detection range, especially in the integration of arrayed sensors where an efficient system solution has yet to be developed.
[0004] Therefore, there is an urgent need to develop a low-cost, green manufacturing process, and flexible piezoresistive sensor with both high sensitivity and array detection capabilities to meet the real-time pressure distribution monitoring needs of wearable devices, smart orthodontic appliances, and other scenarios. Summary of the Invention
[0005] In view of this, the purpose of this invention is to provide a method for fabricating a CuNPs / S-GS / PDMS flexible piezoresistive sensor, so as to solve the problems existing in the background art.
[0006] The fabrication method of the CuNPs / S-GS / PDMS flexible piezoresistive sensor of the present invention includes the following steps: 1) Preparation of CuNPs / S-GS Take 1 mg / mL of graphene dispersion and mix it with 0.15~0.75 wt / v% copper nitrate solution. Add sodium polysulfide solution under nitrogen protection and react at 90~100℃ for 3~8h to generate CuNPs / S-GS precipitate. After washing and drying, obtain black powder CuNPs / S-GS. Sodium polysulfide solution is prepared as follows: 3.2g of sublimed sulfur is added to 50mL of 2.5mol / L Na2S solution, the mixture is stirred for 1-2h, and then filtered to obtain a homogeneous sodium polysulfide solution. The amount of sodium polysulfide solution added is 100~200mL; 2) Preparation of CuNPs / S-GS / PDMS composite foam White sugar and CuNPs / S-GS are mixed at a mass ratio of 30:1 to 50:1, spread on a glass slide and melted to form a sugar template. Then PDMS is poured in, degassed under vacuum and cured at 80±5℃ for 1 to 2 hours. The sugar template is removed by washing with water to obtain CuNPs / S-GS / PDMS composite foam. 3) Component assembly First, the interdigital electrodes are fixed on the surface of the PDMS film. Then, the CuNPs / S-GS / PDMS composite foam is covered on the interdigital electrodes. Finally, the entire assembly is encapsulated with a PET film to obtain a flexible piezoresistive sensor.
[0007] The flexible piezoresistive sensor of the present invention comprises: Flexible substrate: PDMS film; Electrode layer: interdigitated electrodes disposed on the surface of the PDMS film; Sensitive layer: CuNPs / S-GS / PDMS composite foam covering the interdigitated electrodes; Encapsulation layer: A PET film covering the PDMS film, interdigitated electrodes, and sensitive layer to form an overall sealed structure.
[0008] This invention mainly prepared and studied a CuNPs / S-GS / PDMS piezoresistive sensor, explored the effect of CuNPs loading in PDMS foam on the sensor sensitivity, and also investigated the sensor's sensing performance, stability, and practical application in detecting human joint movement.
[0009] The main innovations are as follows: 1. SEM characterization of the composite foam revealed that S-GS and CuNPs were uniformly attached to the interior of the PDMS foam. S-GS, a two-dimensional planar nanomaterial with numerous wrinkles, is well-suited as a carrier material for immobilizing CuNPs, achieving a high-density, uniform loading of CuNPs on its surface. Furthermore, CuNPs can act as bridges connecting adjacent graphene layers, providing a large number of free electrons to S-GS through the CuNPs-graphene interface, thereby increasing the conductivity of the PDMS composite foam by two orders of magnitude. 2. Sensitivity tests revealed that the sensitivity of the CuNPs / S-GS / PDMS composite foam sensor initially increased and then decreased with increasing CuNPs loading. The sensitivity reached its maximum when the CuNPs loading rate was 30 wt%, exhibiting values of 17.78 kPa in pressure ranges of 0-5.06 kPa, 5.06-39.51 kPa, and 39.51-92.25 kPa. -1 0.85 kPa -1 and 0.09 kPa -1 Sensitivity; 3. When a pressure of 80 kPa is applied, the sensor's response time is 0.6 s and its unloading time is 0.81 s. It also exhibits excellent repeatability and stability in a cyclic compression and release test of 2000 cycles, showing a significant improvement over the S-GS / PDMS composite foam piezoresistive sensor. These superior performance characteristics enable the sensor to monitor human joint activity in real time, making it a promising candidate for a wide range of applications. Attached Figure Description
[0010] Figure 1 An optical microscope image of CuNPs / S-GS / PDMS (30wt%) prepared for an embodiment of the present invention.
[0011] Figure 2 SEM images and elemental mapping diagrams of CuNPs / S-GS / PDMS (30wt%) prepared for embodiments of the present invention: (a)-(d) SEM images; (e)-(i) elemental mapping diagrams.
[0012] Figure 3 FTIR spectra of PDMS, S-GS / PDMS and CuNPs / S-GS / PDMS prepared for embodiments of the present invention.
[0013] Figure 4 XRD curves of PDMS, S-GS / PDMS and CuNPs / S-GS / PDMS prepared for embodiments of the present invention.
[0014] Figure 5XPS spectra of CuNPs / S-GS / PDMS prepared for embodiments of the present invention: (a) full spectrum; (b) C 1s; (c) Si 2p; (d) S 2p and (e) Cu 2p.
[0015] Figure 6 Mechanical property curves of CuNPs / S-GS / PDMS composite foam prepared for embodiments of the present invention: (a) stress-strain curve; (b) tensile strain curve.
[0016] Figure 7 The diagram shows the piezoresistive mechanism of the CuNPs / S-GS / PDMS composite foam flexible piezoresistive sensor prepared according to an embodiment of the present invention.
[0017] Figure 8 Sensitivity curves of the CuNPs / S-GS / PDMS composite foam flexible piezoresistive sensor prepared for embodiments of the present invention.
[0018] Figure 9 The resistance change of the CuNPs / S-GS / PDMS piezoresistive sensor under different pressures.
[0019] Figure 10 Test curves of different piezoresistive characteristics of CuNPs / S-GS / PDMS (30wt%) piezoresistive sensor: (a) Stability and repeatability of resistance change rate of piezoresistive sensor under different pressures for 50 cycles; (b) Stability of resistance change rate of piezoresistive sensor under different pressures for 10s; (c) Response curve of piezoresistive sensor to different pressure signals; (d) Response curve of piezoresistive sensor under different compression rates.
[0020] Figure 11 The cyclic stability test curves of the CuNPs / S-GS / PDMS (30wt%) piezoresistive sensor are shown in Figure b: (b) Resistance change rate curve of the pressure sensor after 2000 cycles; (a) and (c) are enlarged views of Figure b.
[0021] Figure 12 The response time of the CuNPs / S-GS / PDMS (30wt%) piezoresistive sensor at 80 kPa.
[0022] Figure 13 Applications of CuNPs / S-GS-PDMS (30wt%) piezoresistive sensors: (a) Photographs of finger bending test and resistance change curves; (b) Photographs of finger bending test and resistance change curves; (c) Photographs of elbow bending test and resistance change curves; (d) Photographs of knee bending test and resistance change curves. Detailed Implementation
[0023] The present invention will be further explained and described below with reference to specific embodiments. Example
[0024] 1. Preparation of CuNPs / S-GS: Disperse 0.20 g of GO in 200 mL of distilled water and sonicate to obtain a GO solution (200 mL 1 mg / mL). Weigh 0.15 g, 0.20 g, 0.30 g, 0.35 g, 0.45 g, and 0.75 g of Cu(NO3)2 and dissolve them in 100 mL of deionized water to prepare Cu(NO3)2 solutions. Mix the GO solution with the Cu(NO3)2 solution, purge with nitrogen gas for 5 min, and then slowly add Na2S dropwise. X The solutions were prepared in batches of 100ml, 115ml, 130ml, 150ml, 180ml, and 200ml, and simultaneously stirred magnetically. The mixtures were then heated in a water bath at 95℃ for 4 hours to obtain a reddish-brown solution containing a black precipitate. The solution was filtered while hot, washed repeatedly with deionized water, and dried in an oven at 80℃ for 2 hours to obtain a black powder, labeled as CuNPs / S-GS (10wt%); CuNPs / S-GS (15wt%); CuNPs / S-GS (20wt%); CuNPs / S-GS (25wt%); CuNPs / S-GS (30wt%); and CuNPs / S-GS (40wt%).
[0025] Among them, Na2S X Solution preparation involved adding 3.2 g of sublimed sulfur to 50.0 mL of a 2.5 mol / L Na₂S solution, stirring for 1 h, and filtering to obtain a homogeneous reddish-brown Na₂S solution. X Solution ((X-1)S8 + 8Na2S → 8Na2S) x The preparation of S-GS only requires the removal of Cu(NO3)2 from the preparation of CuNPs / S-GS.
[0026] 2. Preparation of CuNPs / S-GS / PDMS composite foam Mix 10 g of granulated sugar with 0.33 g of CuNPs / S-GS3, spread the mixture evenly in a petri dish containing a glass slide, and then place it in an oven for slight melting. After cooling, pour a mixture of PDMS (Sylgard 184, A:B = 10:1) and curing agent onto the surface, cover with a glass slide, clamp the two slides together, and then evacuate for 20 min. Then place the sample in an 80°C oven. oAfter curing in an oven at C for 2 hours, the sugar templates were then immersed in distilled water to obtain CuNPs / S-GS / PDMS (10wt%), CuNPs / S-GS / PDMS (15wt%), CuNPs / S-GS / PDMS (20wt%), CuNPs / S-GS / PDMS (25wt%), CuNPs / S-GS / PDMS (30wt%), and CuNPs / S-GS / PDMS (40wt%) composite foams, respectively. The experimental formulations are listed in Table 1. Table 1 PDMS foam formulations with different copper nanoparticle doping amounts 3. Assembly of CuNPs / S-GS / PDMS sensors CuNPs / S-GS3 / PDMS composite foam was cut into 2.0 cm × 2.0 cm pieces. Interdigitated electrodes were placed on the PDMS film as conductive electrodes. The cut composite foam was then transferred to the interdigitated electrodes and finally encapsulated with PET film to obtain a flexible piezoresistive sensor.
[0027] The structural characterization and performance evaluation of the products prepared in the above embodiments are as follows: 1. Structural characterization First, the microstructure of the CuNPs / S-GS / PDMS (30wt%) composite foam was observed under an optical microscope at 100x magnification. The results are as follows: Figure 1 As shown in the figure, the PDMS foam has open pores, and CuNPs / S-GS are dispersed in the PDMS foam.
[0028] Secondly, its morphological features were acquired using scanning electron microscopy (SEM). For example... Figure 2 As shown in (ab), the composite foam exhibits a distinct open-cell structure with rough, crack-free inner walls and a relatively thick outer shell. The pore size is approximately 100 μm-500 μm. From Figure 2 (c) shows that CuNPs are uniformly distributed on the surface of S-GS and PDMS or embedded within PDMS. At higher magnification, the S-GS sheets are thin, translucent, and wrinkled; the CuNPs are hexagonal flakes of uniform size, with opposite sides approximately 1 μm long. Furthermore, no obvious gaps are observed at the phase interface between CuNPs and S-GS, indicating excellent interfacial interactions. Figure 2 (d)). Figure 2 (ei) are the corresponding elemental mapping diagrams in CuNPs / S-GS / PDMS (30wt%) composite foam. It can be seen that C, O, S, N and Cu elements are uniformly distributed in the composite material. This result further indicates the successful loading of CuNPs / S-GS in PDMS foam.
[0029] Figure 3 These are the infrared spectra of PDMS foam, S-GS / PDMS, and CuNPs / S-GS / PDMS composite foam. For CuNPs / S-GS / PDMS composite foam, except for the 2968 cm⁻¹... -1 and 796 cm -1 The absorption peaks correspond to the stretching vibration of CH and the bending vibration of Si-CH3 of methyl groups; at 10¹⁰ cm⁻¹ -1 The absorption peak at 1251 cm⁻¹ corresponds to the tensile vibration of Si-O-Si; -1 Apart from the absorption peak representing the CS stretching vibration, which is the same as that of the S-GS / PDMS composite foam, no other characteristic peaks were observed. This is because in infrared spectroscopy, absorption peaks are usually caused by molecular vibrations and rotations. For metallic copper, its infrared spectrum typically shows a flat baseline without obvious characteristic peaks.
[0030] The crystal structures of S-GS, PDMS, and CuNPs / S-GS / PDMS were analyzed using XRD, and the results are as follows: Figure 4 As shown. Compared with S-GS and PDMS, in the XRD pattern of CuNPs / S-GS / PDMS, except for the characteristic peak of PDMS at 2θ=11° and the weak (002) crystal plane characteristic peak of S-GS3 at 2θ=24°, the diffraction peaks at 2θ=43.3°, 50.4° and 74.1° are consistent with face-centered cubic copper (Cu-PDF#04-0836), corresponding to (111), (200) and (220) crystal planes respectively; the diffraction peaks at 47.6° and 58.9° are consistent with the (20-2) and (202) crystal plane diffraction of CuO (JCPDS 51-1731) respectively; the characteristic diffraction peak at 2θ=36.7° is consistent with Cu2O (JCPDS The diffraction peaks (2θ=36.418°) of 05-0667 are consistent with those of the crystal plane diffraction at (111). This proves that CuNPs and S-GS were successfully added to the PDMS composite foam, and that the composite material contains a certain amount of CuO and Cu2O.
[0031] The elemental composition and chemical state of CuNPs / S-GS / PDMS samples were analyzed using XPS characterization, and the results are as follows: Figure 5 As shown. Figure 5(a) shows the full spectrum of the CuNPs / S-GS / PDMS sample, which reveals the presence of S 2p (119.1 eV), C 1s (284.1 eV), O 1s (531.1 eV), Si 2p (101.1 eV), and Cu 2p (978.1 eV) peaks. Figure 5 In the C 1s spectrum shown in (b), the characteristic peaks near the binding energies of 283.7 eV, 285.2 eV, 286.2 eV and 287.8 eV are attributed to C-Si, CC / C=C, CO and C=O groups, respectively. Figure 5 In (c), the Si 2p spectrum shows two significant peaks at 101.2 and 102.6 eV, respectively, associated with CO-Si and Si-O-Si. Figure 5 In (d), the S 2p spectra near 164.7, 166.9, and 169.3 eV are attributed to elemental sulfur, thiophene sulfur, and sulfonate, respectively. Figure 5 (e) The Cu 2p spectrum shows two characteristic peaks at 932.0 eV and 951.5 eV, which correspond to the binding energies of Cu 2P3 / 2 and Cu 2P1 / 2 in Cu and Cu2O, respectively. Because the signal peaks of Cu and Cu2O are very close, XPS cannot completely distinguish between them. The characteristic peaks at 933.8 eV and 954.5 eV correspond to the binding energies of Cu2P3 / 2 and Cu2P1 / 2 in CuO, respectively. The remaining peaks are likely companion peaks or satellite peaks. This XPS spectrum indicates that the composite material contains a certain amount of CuO and Cu2O, which is consistent with the XRD characterization results.
[0032] 2. Performance Evaluation 2.1 Mechanical Properties To evaluate the effect of CuNPs mass percentage on the mechanical properties of CuNPs / S-GS / PDMS composite foam, compression and tensile properties were tested on six groups of composite foams with different CuNPs mass percentages, and compared with pure PDMS and S-GS / PDMS composite foams. Figure 6As shown in (a), under a 20% strain condition, pure PDMS, S-GS / PDMS composite foam, and samples with different CuNPs percentages all exhibited similar stress-strain curves. Under the same deformation, PDMS foam still showed the lowest compressive stress, indicating its excellent elasticity. Under the same reaction conditions, as the mass percentage of CuNPs increased from 10wt% to 40wt%, the maximum compressive stress gradually increased to 25.7 kPa, 32.4 kPa, 40.6 kPa, 44.4 kPa, 46.2 kPa, and 57.2 kPa, respectively. This is because CuNPs themselves possess high elastic modulus and hardness, and their addition may improve the overall elastic modulus and hardness of the composite material. Figure 6 (b) Tensile stress-strain curves of eight samples are shown. As can be seen from the figure, the elongation at break of CuNPs / S-GS / PDMS increased from 37% (S-GS / PDMS) to 77% (CuNPs / S-GS / PDMS (40wt%)). The above results indicate that the addition of CuNPs can improve the mechanical properties of PDMS composite foam.
[0033] 2.2 Sensing Performance 1) Electrical conductivity The resistance of CuNPs / S-GS / PDMS composite foam was tested using a digital multimeter, and its conductivity was calculated. The data are shown in Table 2. Table 2 Electrical conductivity of S-GS / PDMS composite foam In a series of experiments with varying CuNPs mass percentage, CuNPs / S-GS / PDMS (30wt%) exhibited the highest conductivity, reaching 4.23 × 10⁻⁶. -5 S·m -1In the S-GS / PDMS composite foam piezoresistive sensor, S-GS provides the conductive path, with charge hopping between S-GS sheets. Adding CuNPs, due to their superior conductivity compared to S-GS, provides additional conductive channels for the composite foam, thus reducing its overall resistance. Furthermore, S-GS and CuNPs exhibit a synergistic effect; their contact may create a mechanism that synergistically enhances conductivity, allowing the conductive paths of S-GS and CuNPs to change together under external pressure, forming a more complete conductive network. In summary, a higher mass percentage of CuNPs results in better conductivity of the composite foam. However, excessive CuNP loading in the PDMS foam can lead to stacking and aggregation. This aggregation may disrupt the previously formed conductive network, reducing the number of effective conductive paths and lowering the conductivity in the CuNPs / S-GS / PDMS composite foam.
[0034] The working mechanism of the CuNPs / S-GS / PDMS composite foam flexible piezoresistive sensor is mainly based on the material properties and piezoresistive effect of CuNPs, S-GS, and PDMS in the functional layer. During the sensing performance test, when the sensor is not under pressure, the conductive fillers adhere loosely to the PDMS foam, and the conductive path is as follows: Figure 7 As shown by the blue line, the structure consists of three types: CuNPs with CuNPs, CuNPs with S-GS, and S-GS with S-GS. These are relatively few in number and spaced far apart. When the sensor is subjected to external pressure, the deformation of the PDMS substrate causes changes in the arrangement and shape of the internal S-GS and CuNPs, creating more conductive paths, such as... Figure 7 As shown by the red line, the quantity is more increased and denser than that of the blue line, which leads to a decrease in the resistance of the composite foam and an increase in the rate of change of resistance. Once the pressure is removed, the PDMS substrate will return to its original state, the conductive channels will also return to their original state, and the resistance value will return to its original state, thus realizing the sensing of pressure.
[0035] 2) Sensitivity Sensitivity tests were performed on the CuNPs / S-GS / PDMS composite foam piezoresistive sensor, and the results are as follows: Figure 8As shown. Using linear fitting, the sensitivity curve of the CuNPs / S-GS / PDMS composite foam piezoresistive sensor can be roughly divided into three linear regions, corresponding to three different sensitivity values. Comparison of the sensitivities of the six sensors reveals that, under different pressure ranges, the sensor sensitivity initially increases and then decreases with increasing CuNPs mass percentage. The sensor prepared from the CuNPs / S-GS / PDMS (30wt%) composite foam, which has the highest conductivity, exhibits the highest sensitivity: 17.78 kPa in the 0-5.06 kPa range. -1 Within the range of 5.06-39.51 kPa, the sensor's sensitivity is 0.85 kPa. -1 Within the range of 39.51-92.25 kPa, the sensor's sensitivity is 0.09 kPa. -1 In summary, the CuNPs / S-GS3 / PDMS (30wt%) composite foam piezoresistive sensor integrates high conductivity and sensitivity, exhibiting excellent sensing potential. Therefore, this sensor was used for measurements in subsequent stability, response / recovery time, and application tests.
[0036] 3) Stability To investigate whether the sensor can function properly under dynamic pressure, a CuNPs / S-GS / PDMS (30wt%) composite foam flexible piezoresistive sensor was subjected to load tests at 1-90 kPa. The test results are as follows: Figure 9 As shown. In the 11 sets of experiments, when the pressure was 1 kPa, 2 kPa, and 4 kPa, the rates of change of resistance were 12.6%, 20.4%, and 58.1%, respectively. Figure 9 (a)); When the pressure is 8 kPa, 10 kPa, 20 kPa, 30 kPa and 40 kPa, the rate of change of resistance is 77.4%, 83.4%, 90.6%, 94.7% and 96.6%, respectively. Figure 9 (b) When the pressure is 60 kPa, 80 kPa and 90 kPa, the rate of change of resistance is 97.6%, 98.1% and 98.5%, respectively. Figure 9 (c) As can be seen from the figure, the CuNPs / S-GS / PDMS (30wt%) piezoresistive sensor can adapt to different pressure working environments and has a smooth curve, demonstrating good stability, which proves its reliability in pressure detection applications.
[0037] To further demonstrate the operational stability of the CuNPs / S-GS / PDMS (30wt%) composite foam flexible piezoresistive sensor, Figure 10(a) shows the rate of change of resistance after 50 cycles at pressures of 2 kPa, 8 kPa, 10 kPa, 20 kPa, 40 kPa, and 80 kPa. The graph shows that the rate of change of resistance of the sensor fluctuates little after every 10 cycles at different pressures. Figure 10 (b) shows the electrical characteristic curves obtained when the sensor is held under pressures of 2 kPa, 8 kPa, 10 kPa, 20 kPa, 40 kPa, and 80 kPa for 10 s. As can be observed from the figure, the rate of change of the sensor's resistance remains essentially constant during the pressure holding process. Figure 10 (c) is a data graph obtained after conducting a phased pressure loading experiment on the sensor. Using a universal testing machine, pressures of 2 kPa, 8 kPa, 10 kPa, 20 kPa, 40 kPa, and 80 kPa were sequentially applied to the sensor in a static state, with a pause at each pressure. The graph shows that the rate of change of the sensor's resistance increases with increasing pressure, while the rate of change remains essentially constant during the pause period. Figure 10 (d) shows the sensor's response at different compression rates while maintaining a pressure of 10 kPa. The response signals at compression rates of 5 mm / min, 10 mm / min, and 50 mm / min are relatively stable, and the resistance change rate is also essentially the same. These data demonstrate that the sensor exhibits superior stability compared to the S-GS / PDMS sensor, and also prove its potential for application in complex stress conditions.
[0038] To test the operating life of the CuNPs / S-GS / PDMS (30wt%) composite foam piezoresistive sensor, Figure 11 This is a resistance change rate curve obtained from 2000 continuous cyclic compression tests on the sensor at 80 kPa. It can be seen that the resistance change rate of the sensor did not change significantly during multiple load cycles under the same pressure, indicating that the sensor can withstand fatigue testing. Two segments were randomly selected from the 2000 cycles for magnified analysis. Figure 11 (a) and (c) show that the resistance change rate of the sensor remains within the range of 0-98%. During the cycle, the resistance change rate does not fluctuate significantly, exhibiting more stable characteristics, which indicates the feasibility of adding CuNPs material.
[0039] 4) Response / Recovery Time To verify the sensor's rapid and immediate response to pressure, a pressure of 80 kPa was applied to the CuNPs / S-GS / PDMS (30wt%) composite foam piezoresistive sensor, and then released. This process was repeated five times. The change in the sensor's resistance and the time it took for the sensor to respond to the signal were recorded using a digital multimeter. The results are as follows: Figure 12 As shown, the sensor resistance changes zero under no pressure load. When pressure is applied, the sensor responds rapidly with a response time as low as 0.6 s. After the pressure is removed, the sensor resistance recovers in 0.81 s. Furthermore, in five repeated experiments, the sensor resistance remained constant before and after being subjected to pressure, demonstrating good stability.
[0040] 3. Application Exploration Based on a CuNPs / S-GS / PDMS (30wt%) piezoresistive sensor, this paper also conducted a series of practical application tests. The sensor was placed on the finger surface of a 26-year-old woman, as... Figure 13 As shown in (a), the rate of change of resistance curves clearly reflect the degree of bending and the time interval when the finger is bent and released. Furthermore, the sensor can also detect the wrist (…). Figure 13 (b) Elbow ( Figure 13 (c) Knee ( Figure 13 (d) Bending. Specifically, when the joint bends, the sensor's resistance decreases, and when the joint relaxes, the sensor's resistance increases. Therefore, this sensor has good application potential in real-time monitoring of human activity and correcting incorrect human postures.
Claims
1. A method for fabricating a CuNPs / S-GS / PDMS flexible piezoresistive sensor, characterized in that, Includes the following steps: 1) Preparation of CuNPs / S-GS A 1 mg / mL graphene dispersion was mixed with a 0.15–0.75 wt / v% copper nitrate solution. Sodium polysulfide solution was added under nitrogen protection, and the mixture was reacted at 90–100 °C for 3–8 h to generate CuNPs / S-GS precipitate. After washing and drying, a black powder of CuNPs / S-GS was obtained. The sodium polysulfide solution was prepared as follows: 3.2 g of sublimed sulfur was added to 50 mL of a 2.5 mol / L Na₂S solution, and the mixture was stirred for 1–2 h. After filtration, a homogeneous sodium polysulfide solution was obtained. The amount of sodium polysulfide solution added was 100–200 mL. 2) Preparation of CuNPs / S-GS / PDMS composite foam White sugar and CuNPs / S-GS are mixed at a mass ratio of 30:1 to 50:1, spread on a glass slide and melted to form a sugar template. Then PDMS is poured in, degassed under vacuum and cured at 80±5℃ for 1 to 2 hours. The sugar template is removed by washing with water to obtain CuNPs / S-GS / PDMS composite foam. 3) Component assembly First, the interdigital electrodes are fixed on the surface of the PDMS film. Then, the CuNPs / S-GS / PDMS composite foam is covered on the interdigital electrodes. Finally, the entire assembly is encapsulated with a PET film to obtain a flexible piezoresistive sensor.
2. A CuNPs / S-GS / PDMS flexible piezoresistive sensor prepared by the method described in claim 1, characterized in that, include: Flexible substrate: PDMS film; Electrode layer: interdigitated electrodes disposed on the surface of the PDMS film; Sensitive layer: CuNPs / S-GS / PDMS composite foam covering the interdigitated electrodes; Encapsulation layer: A PET film covering the PDMS film, interdigitated electrodes, and sensitive layer to form an overall sealed structure.
3. The application of the CuNPs / S-GS / PDMS flexible piezoresistive sensor as described in claim 2 in human motion monitoring.
Citation Information
Patent Citations
A flexible piezoresistive sensor and its application
CN112086553B
Sulfur-base composite material containing graphene and preparation method thereof
CN102368553A
Graphene / nanometer copper electric conducting composite material and preparation thereof
CN102436862A
Composite conductive material of graphene film and metal nanometer structure and preparation method thereof
CN104616717A
Preparation method and application of Cu nanowire-reduced graphene oxide three-dimensional porous film
CN105583408A